Cerebral Protection During Coronary Artery Bypasses Grafting in Bilateral Total Internal Carotids Occlusion: Case Report - Froutan, Afshin; Rezvan Nobahar, Mohammad; Rahimian, Hossein; Chegini, Azita; Behnaz, Faranak (Annals of Anesthesiology and Critical Care, 2019)
Introduction: The best management for the patient with coronary artery disease (CAD) that requires emergent coronary bypass graft surgery (CABG) with bilateral total internal carotid artery occlusions previously reported. Here we report two successful cases of CABG with additional occlusion in the circle of Willis anterior or posterior communicating artery “incomplete cow” with onpump technique and cerebral protection considerations. Case Presentation: Bilateral carotid artery occlusion, coronary artery disease, and emergency operation with cardiopulmonary bypass are associated with increased stroke, especially when there is one additional occlusion of the cerebral artery in the circle of Willis. Routine preoperative carotid artery sonography and selective carotid angiography revealed bilateral total carotid occlusion in both cases in addition, CT-angiography also confirmed occlusions of right posterior communicating in the first case and left posterior communicating artery in the second case. Collateral circulation feeding in the intracranial circulations originated mainly from the vertebrobasilar system (compensatory phase) preoperative physical examinations showed no neurological deficit. Operation was done successfully with moderate hypothermia and different cerebral protection considerations and postoperative courses were uneventful and patients discharged from hospital seven days post operation. Conclusions: Anesthesia should consider hemodynamic management and avoid significant tachycardia or bradycardia and severe hypertension or hypotension.